Vastus medialis injury by indirect mechanism in football, a case series - Oscar Vicente; Carles Pedret; Olga Velasco (Apunts Sports Medicine)
Introduction: To our knowledge, indirect mechanism injuries of the Vastus medialis (VM) are still not reported in literature. The aim of this case series study is to describe indirect mechanism VM injuries in football, suggest the best clinical assessment, imaging tests and guidelines for a safe return-to-play (RTP). Materials and methods: Over a period of 3 years, four professional football players diagnosed with VM injury by indirect mechanism, were included in the series. Magnetic resonance imaging (MRI) was performed to control the injuries evolution. Results: In this series, Myofascial injuries presented higher frequency and shorter RTP time (16 days mean) than myotendinous injury (26 days). Two injury mechanisms were identified: Deceleration and progressive loading. Conclusion: The VM is a muscle that can also be injured by indirect mechanism. These are a good prognosis injury, if managed correctly, as they are clinically well tolerated injuries. The series findings should be taken wisely, requiring further sampling and studies.